Oxygen saturations of medical inpatients in a Malawian hospital: cross-sectional study of oxygen supply and demand. Issue 1 (December 2012) - Evans, Hywel-Gethin; Mahmood, Nadia; Fullerton, Duncan; Rylance, Jamie; Gonani, Andrew; Gordon, Stephen; Mortimer, Kevin; Allain, Theresa
Abstract Oxygen is a World Health Organisation listed essential drug yet provision of oxygen in developing countries often fails to meet demand. The aim of this study was to evaluate the need for supplementary oxygen against oxygen delivery capacity at a large teaching hospital in Malawi. A cross-sectional study of all adult medical inpatients and assessment of oxygen provision over a 24-hour period was conducted. 144 patients were included in the study, 14 of whom met local and international criteria for oxygen therapy (oxygen saturations of <90%). Four were receiving oxygen. Of the 8 oxygen concentrators available, only 4 were functional. In conclusion, we identified a need for oxygen that was greater than the supply.